DEGUMMING MINYAK WIJEN (Sesamum indicum L.) DENGAN MEMBRAN ULTRAFILTRASI - , SURYANI UNE, STP ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Crude sesame oil was extracted from roasted and pressed sesame seeds. Utilization of sesame oil without removing of phosphatides compound from oil with degumming process causing loss of quality and influencing the consumer acceptance. The objectives of this research were to assess the performance membrane for degumming sesame oil and to determine the effect of miscella concentration on permeat flux, membrane rejection values, phosphor level, free fatty acid, peroxide value and color of produced sesame oil. The research was conducted by preparation of sesame oil by roasting sesame seed at 180oC for 30 minutes and subsequently it was pressed by hydraulic press at 140 kN for 5 minutes. Miscella of sesame oil in hexane was prepared by mixing sesame oil and hexane with concentration of 20, 25, and 30%, respectively. Furthermore, sesame oil miscella was degummed using ultrafiltration membrane PES and PVDF. The characteristics of sesame oil was analyzed. Collected data was statistically analyzed by using program of Statistical Product and Service Solution (SPSS) number 16. The crude sesame oil showed yield 40,38 ± 1,12 %, moisture content 0,013 ± 0,00 % (db), phosphor 11,49 ±0,01 ppm, peroxide value 1,46 ± 0,17 meq O2/kg, free fatty acid 1,21 ± 0,01 (%), and red color 4,1 Lovibond, yellow color 8 Lovibond. The best sesame oil was produced from miscella concentration and degummed by 25% using ultrafiltration membrane PVDF 20.000 Da.